Chain Routing Algorithm of Wireless Sensor Networks for Streetlight Monitoring System - Tiaojuan Ren; Yourong Chen; Zhangquan Wang (Dianxin kexue)
To save network node energy consumption and reduce data transmission delay in streetlight monitoring system, a chain routing algorithm for wireless sensor network（CRASMS）was proposed. The algorithm divided the monitoring region into several clustering regions according the information of nodes and monitoring region, successively and circularly selected a node to the cluster head node in each clustering region, established the star network in each cluster by the communication of cluster head node and sensor node. Finally, cluster head node received the data of sensor nodes, used the data fusion algorithm to reduce data redundancy, transmitted the fused data to sink node with multi-hop routing among cluster head nodes and transmitted the client's commands to the controlled nodes. The simulation results show that CRASMS algorithm keeps the advantage of PEGASIS algorithm in terms of energy consumption and the advantage of LEACH algorithm in terms of data transmission delay, overcomes the lack of PEGASIS algorithm in terms of data transmission delay and the lack of LEACH algorithm in terms of node energy consumption. It keeps the average node energy consumption and the average data transmission delay at a low level. Under certain conditions, CRASMS algorithm outperforms LEACH and PEGASIS algorithms.